Theta and gamma oscillations in the rat hippocampus support the discrimination of object displacement in a recognition memory task - Neves, Lívia; Lobão-Soares, Bruno; Araujo, Ana Paula de Castro; Furtunato, Alan Michel Bezerra; Paiva, Izabela; Souza, Nicholy; Morais, Anne Kelly; Nascimento, George; Gavioli, Elaine; Tort, Adriano Bretanha Lopes; Barbosa, Flávio Freitas; Belchior, Hindiael (Frontiers in Behavioral Neuroscience, 2022)
Episodic memory depends on the recollection of spatial and temporal aspects of past experiences in which the hippocampus plays a critical role. Lesion studies in rodents have shown that the dentate gyrus (DG) and CA3 subfields are necessary to detect object displacement, a process known as pattern separation. Despite these findings, the real-time oscillatory activity underlying memory discrimination of subtle and pronounced object displacements is still poorly understood. Here, we chronically implanted 16 electrodes across the layers of the dorsal hippocampus to bilaterally record network oscillations in the DG, CA3, and CA1 while rats executed an object recognition task with high (HD, 108 cm) and low spatial displacement (LD, 54 cm) tests. Behavioral analysis revealed that animals discriminated between stationary and displaced objects in the HD test but not in the LD test. We analyzed oscillatory activity specifically during object exploration and found strong rhythmic activity in the theta frequency (5-12 Hz) band in the three hippocampal subfields. When we compared HD and LD tests, we found higher theta power in DG and higher theta peak frequency in CA3 during the HD test. Moreover, the theta-slow-gamma phase-amplitude coupling was higher during HD than LD tests in the DG and CA3. Theta-slow-gamma modulation at both DG and CA3 were directly correlated to the preference for displaced objects (to the discrimination index) in HD tests. Similarly, within the HD test, we found higher theta power during the exploration of displaced than stationary objects in DG and CA3. We thus conclude that successful memory discrimination for object displacement is supported by the coordination of theta and gamma oscillations in the DG and CA3 regions of the hippocampus.